(untitled) - Nakanishi, Susumu (Tokyo, Japan, 2019)
This book introduces a balanced mix of new and old words that reflect the singular beauty of the Japanese language. The beautiful words of the Japanese language are not—as some people say—simply old, antiquated terms. Discerning beauty in a language requires more than having an antiquarian's ear; it requires certain sensibilities and sensitivities. Only by submerging ourselves in a language can we perceive its splendid subtleties, and appreciate its true beauty. This book offers readers an opportunity to delve into to those nuances of Japanese, explore the language's history, and savor its unique beauty.
Keywords: Tiếng Nhật,Japanese language; Từ nguyên,Etymology